Penindasan (Bullying) Di Sekolah - Sekar, Dwi Amalia Chandra (Jurnal Ilmu Kesejahteraan Sosial, 2007)
The aim of this article is to give some information and attempt to raise awareness about behavior problem among children in or around the school in terms of abuse or intimidation (bullying). School as intitution, gives knowlege and skill to develop positive self-potential for students cannot be completedly reached. For the children who became the victim, schools are no longer can give them feeling secure and hapiness. School bullying occured long time, but there is only small attention from school, parents, communities, because they considered it as a normal behavior dan become tradition in school. Bullying can bring fear and hopelesness into life. Sadly, people pay attention when the victim committed suicidot death because physical abuse. This article explains about defining bullying, types of bullying, characteristic of bullies and the victims, and away to prevent and stop bullying.